STUDI DINAMIKA POPULASI KELELAWAR KUBAR JANGGUT-HITAM (Taphozous melanopogon Temminck, 1841) DI GUA SRUNGGO DI KAWASAN KARST TUBAN - Tatag Bagus Putra Prakarsa; Kurnia Ahmadin (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Abstract- This research was aimed to determine fluctuation of  Taphozous melanopogon population in Srunggo cave in Tuban karstic area. The research began in 2010 until 2012 in Srunggo cave in Tuban karstic area of eastern Java.  This research is ecological research with this type of research, Natural Trajectory Experimment  (NTE), population-local spatial scale, and one-generation temporal scale. Data was taked by line potret method (evening emergence count modification), twice in dry monsoon and rainy season everi years. Research data analysed by descriptive. Srunggo cave is a cave with single population of  Taphozous melanopogon. Population fluctuation this species between 2010 until 2012 that are 2126, 1946, and 1832 individu. The Population trend is decrease. That caused by human disturbance in habitat and illegal hunting by local people. The population during the rainy season in three years is likely to decrease, compared to the dry season. It is possible that the species population is metapopulasi.  Keywords: Population, Bat, Taphozous melanopogon, Karst, Biospeleology